Acute appendicitis in intestinal malrotation. Case report. - Febres Ramos, Richard J. (2020)
Intestinal malrotation is a congenital abnormality of the embryological rotation of the intestine, it is estimated that more than 90% of patients with intestinal malrotation will be presented in the first 12 months of life. The clinical presentation in adults is manifested in a progressive way that usually occurs during the postprandial period, presenting: intermittent vomiting, abdominal pain, weight loss, chronic diarrhea, peritonitis, food intolerance, among Another. Treatment will depend on presentation, either acute or chronic, requiring emergency laparotomy to determine the cause. There is a case of acute surgical abdomen for acute appendicitis in a 27-year-old patient with intestinal malrotation, with initial clinical presentation of severe abdominal pain, diarrhea, positive lumbar percussion fist, which finally reached a Proper resolution and a good prognosis.